2004
DOI: 10.1002/jgm.675
|View full text |Cite
|
Sign up to set email alerts
|

AdVEGF165 gene transfer increases survival in overdimensioned skin flaps

Abstract: Our results confirm the important role of VEGF(165) on angiogenesis in ischemic flaps. Indeed by injecting VEGF(165) at 3 to 7 days preoperatively in a concentration of 1 x 10(9) pfU our data show that length-to-width ratio for random-pattern-flaps could be increased from 2 : 1 to 3 : 1 and therefore may allow a wider range of applications of this simple flap technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 34 publications
2
42
0
3
Order By: Relevance
“…[34][35][36][37] The benefits of enhanced angiogenesis have primarily been shown in models of impaired wound healing 28,32,33 or severe injury. [29][30][31] In contrast, several reports have shown that modulation of angiogenesis does not affect epidermal healing rates or overall wound closure to a great degree, [38][39][40][41][42][43] and some studies have even reported enhanced healing with reduced angiogenesis. 44 Thus, although there are many studies examining angiogenesis and wound repair, the degree to which angiogenesis actually facilitates healing under normal circumstances is still not known.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[34][35][36][37] The benefits of enhanced angiogenesis have primarily been shown in models of impaired wound healing 28,32,33 or severe injury. [29][30][31] In contrast, several reports have shown that modulation of angiogenesis does not affect epidermal healing rates or overall wound closure to a great degree, [38][39][40][41][42][43] and some studies have even reported enhanced healing with reduced angiogenesis. 44 Thus, although there are many studies examining angiogenesis and wound repair, the degree to which angiogenesis actually facilitates healing under normal circumstances is still not known.…”
Section: Discussionmentioning
confidence: 97%
“…It is not surprising then, that many studies have found angiogenesis to be beneficial for wound repair. Stimulation of angiogenesis can enhance healing rates, [27][28][29][30][31][32][33] whereas a reduction in angiogenesis can impair the same. [34][35][36][37] The benefits of enhanced angiogenesis have primarily been shown in models of impaired wound healing 28,32,33 or severe injury.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF, which is physiologically secreted by fibroblasts and inflammatory cells [6], has also been shown to influence *E-mail: e.maeda@eng.hokudai.ac.jp (EM) angiogenic process [7,8]. It was reported that VEGF has the ability of changing EC shape during vascular lumen formation [9].…”
Section: Introductionmentioning
confidence: 99%
“…Flaps with ratios greater than 2:1 have been shown to exhibit ischemia in distal regions due to decreased proximity to the pedicled end [12,13]. Studies conducted in rats bearing overdimensioned 4:1 random-pattern fl aps demonstrated ischemia in distal halves of fl aps that, over time, led to fl ap necrosis in those regions [12,13].…”
mentioning
confidence: 99%
“…Studies conducted in rats bearing overdimensioned 4:1 random-pattern fl aps demonstrated ischemia in distal halves of fl aps that, over time, led to fl ap necrosis in those regions [12,13]. In this study we create over-dimensioned 4:1 random-pattern local fl aps in a murine model, anticipating a loss of perfusion in the distal halves of fl aps.…”
mentioning
confidence: 99%